0217 Mesothelioma and cancer of the pleura deaths – recovering missing cases from hospital records. (21st August 2017) - Santana, Vilma; Algranti, Eduardo; Campos, Felipe; Cavalcante, Franciana; Lorenzi, Ricardo; Inamine, Rosemairy; Souza, William; Santos, Simone
Abstract : Background: Mesothelioma is a rare cancer of high lethality associated with asbestos exposure. In several studies mesothelioma and cancer of the pleura (MCP) are analysed together because misdiagnoses or coding errors between them are common. Undercounting and underreporting of these diseases have been demonstrated, particularly where access to diagnostic resources is poor as for developing countries. Objective: To examine the performance of a probabilistic linkage used to match data from death certificates (Mortality Information System) to deaths reported in hospital records (Authorisation of Hospital Admissions of the National Health System). Methods: Cases with diagnosis coded as C45.0 - C45.9 and C38.4 (International Classification of Diseases 10thRevision) were selected from each anonymous database from 2002 to 2012, Brazil. After probabilistic linkage, matched and unmatched cases were combined in a single individual database. Linkage performance was examined by confirming matched cases based on similar datasets which includes full names, available only for the São Paulo state. Results: A total of 1059 MPC cases were found, 718 (71.7%) with records only in the Mortality Information System, 277 (23.6%) registered exclusively in the hospital database, and 57 (5.7%) matched with data in both databases. The majority of hospital unmatched cases had other cancer diagnosis as the underlying cause of death (87.4%). Linkage failed to match only five cases due to inconsistencies in birth dates or gender records. Conclusions: Probabilistic linkage can be a tool to recover missing cases of MCP in death certificates using hospital admissions records in Brazil.